Day-Flying Lepidopteran Species Abundance, Diversity, and Distribution in Wolaita Sodo University, Ethiopia - Abenezer Wendimu; Wondimagegnehu Tekalign; Elias Bojago (Psyche: A Journal of Entomology)
Lepidoptera account for the second largest, most diverse, widespread, and widely recognized insect order in the class Insecta. At four microhabitats at Wolaita Sodo University (WSU) in Ethiopia, lepidopteran diversity and abundance were studied for the first time using transects between January 2022 and December 2023. Data were analyzed using analysis of variance, correlation analysis, diversity indices, and ordination and cluster analysis. Altogether 50 species of 367 individuals were collected throughout the study period distributed in 6 families. The Nymphalidae family contained the highest species abundance 20 (34%). In comparison to other ecosystems, open forest regions (35%) included more species, followed by shrub forest (30%). Species such as Danaus plexippus, Tirumala septentrionis, and Melanargia lachesis were abundant in open forest habitat. Idea leuconoe and Eurema brigitta were also abundant, regardless of location. About 36% of species were recorded only in dry season and 36% of total were recorded only in wet season. Spearman’s rho correlation analysis showed that butterfly families had strong positive relationships with flying habitat and flight seasons. Therefore, adequate conservation measures should be taken to ensure their survival, as well as the preservation of their habitats for the benefit of the ecosystem as a whole.